Defining water-related energy for global comparison, clearer communication, and sharper policy. (1st November 2019) - Kenway, Steven J.; Lam, Ka Leung; Stokes-Draut, Jennifer; Sanders, Kelly Twomey; Binks, Amanda N.; Bors, Julijana; Head, Brian; Olsson, Gustaf; McMahon, James E.
Abstract: The need for energy in water provision and use is obvious, however the drivers are often complex, difficult to assess, and often inconsistently presented. Here we build a clearer definition and conceptual framework of "water-related energy". We apply this framework to harmonise data and results across disparate studies so that regional estimates of water-related energy can be compared in a consistent way for the first time. We show how widely different boundaries have been used for analysis including or excluding: water and wastewater utilities, as well as residential, commercial, industrial, and agricultural water users. Consequently, understanding of what constitutes "water-related energy" is widely divergent. We demonstrate how up to 12.6% of total national primary energy use can be influenced by water, when (i) water-related energy of water users, and (ii) energy use by water utilities, are all included. Water heating for residential, commercial, and industrial purposes is the dominant fraction. Water and wastewater utilities use 0.4–2.3% of primary energy or 0.6–6.2% of regional electricity, mostly for water pumping. This is substantial, but lower than frequent claims in the media and reports. To answer how is miscommunication influencing policy? we undertake a novel systematic tracking of communication to demonstrate distortion between research and its application in government reports, media and policy. We show that significant confusion is caused by (i) unclear or inconsistent boundaries (ii) widely differing use of terms for water "system", "sector", and "supply", (iii) frequent failure to distinguish 'energy' from 'electricity' and (iv) wide use of non-standard units. While acknowledging that media is often less accurate than government reports, and that peer-reviewed articles generally have highest overall quality, we observe miscommunication and inconsistency in all publication forms. We argue a global protocol is needed to improve consistency of analysis and sharpen policy towards sustainable water end use because this is where most water-related energy occurs. We establish a foundational framework and definitions for this protocol while recognising much more needs to be done. The strong practical and theoretical implications of the work for sustainable cleaner production are elucidated. This is timely, as global quantification of water-related energy has yet to occur particularly for water end-use which is the dominant component. Graphical abstract: Image 1 Highlights: New framework developed for analysis of water-related energy. Demonstrates water users and providers account for 6–12% primary energy use. Utilities account for 0.4–2.3% of primary energy or 0.6–6.2% of regional electricity. Novel tracking of miscommunication of water-related energy into policy. Global 'water-related energy "protocol proposed including definitions and inclusions.